SIMULASI AKSESSIBILITAS EVAKUASI TSUNAMI MENGGUNAKAN TOOLS NETWORK ANALYSIS DI DAERAH RAWAN TSUNAMI KABUPATEN TANGGAMUS - Moh Muhaemin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2023)
Geological activity in the Sunda Strait received attention through the tsunami that occurred at the end of 2018 and the tectonic earthquake in the Sunda Strait subduction zone with Magnitude 6.9 on August 2, 2019. These conditions raise concerns about the threat of earthquake and tsunami disasters in the surrounding area. Tanggamus Regency, which is located within a fairly close radius to the Sunda Strait, has a very wide tsunami-prone lowland, especially in the area around the tip of Teluk Semangka. Based on these conditions, this research generally aims to map evacuation service areas, map evacuation times, and analyze effective evacuation models. To answer these challenges, this research was conducted following several methodological stages. It started with defining the study area using spatial analysis, digitizing the road network and interlinking it with the Network Analysys tool on the ArcGIS platform. Based on the observation, it was found that the most at-risk areas are those that have the farthest distance from the Temporary Evacuation Site (TES) location when traveled without a vehicle. Each region has a TES location that can be reached using the available roadways. There are 3 sub-districts that have a travel time of more than 30 minutes to reach the TES, namely, Semaka sub-district, Wonosobo sub-district and Kota Agung Barat sub-district. It is expected that the results of this study can be one of the considerations in tsunami disaster mitigation efforts in Tanggamus Regency.